TOLERANCE AT SEEDLING STAGE IN POLYETHYLENE GLYCOL - A. Bibi; H. A. Sadaqat; M. H. N. Tahir; H. M. Akram (Journal of Animal and Plant Sciences, 2012)
Twenty different accessions of sorghum (Sorghum bicolor var Moench) were evaluated for their genetic potential to drought tolerance at seedling stage. Water stress was simulated by non-ionic water soluble polymer polyethylene glycol of molecular weight 6000. After fourteen days data were recorded for easily measurable seedling traits as shoot length, root length, fresh shoot weight, dry shoot weight, fresh root weight and dry root weight under control as well as water stress conditions. Significant differences were observed among the accessions, treatments and their interactions for evaluated plant traits suggesting a great amount of variability for drought tolerance in sorghum. Differential sensitivity of seedling traits was noted due to water stress created by PEG. However, shoot related traits were the most sensitive against the water stress. Proportional contribution of RL, SL, FSW, DSW, FRW and DRW was 56.6%, 20.2 %, 10.5%, 8.5%, 3.5% and 0.7% to drought stress as measured by Principle component analysis. Root length (56.6%) was the highest towards drought tolerance, indicating root length was least effected by water stress among all the seedling traits. The most promising drought tolerant accessions (80353, 80365, 80199, 80204 and 80319) were screened through multivariate scoring index.
Keywords: Sorghum bicolor L.; Polyethylene glycol (PEG); water stress; seedling traits